Strategi Dan Desain Dakwah Untuk Menangkal Faham Radikalisme Dan Intoleransi Di Kabupaten Boyolali - Jalari, Muhammad; Hendratmoko, Christiawan; Falaah, Muhammad Fajrul; Nurtantiono, Andri; Kurnianingsih, Heny (Jurnal Gema Ngabdi, 2025)
This community service activity took the form of counseling and dialogue between resource persons and community leaders, preachers, and female Islamic educators (daiyah) in Boyolali to address the emergence of extremist attitudes leading to radicalism and intolerance. These erroneous political and religious stances disrupt harmonious religious and national life. To safeguard the integrity of the Unitary State of the Republic of Indonesia (NKRI), it is crucial to develop effective preaching strategies and designs. The activity was facilitated through a partnership with the Boyolali Regency Ministry of Religious Affairs and received logistical support from the Boyolali Regency BAZNAS (National Alms Agency), with funds allocated from ZIS (Zakat, Infaq, and Sadaqah) for asnaf sabilillah (those in the cause of Allah) as regulated by law. The method employed was counseling packaged as Tazwidul Muballighin, focusing on strategies and designs for preaching that embody rahmatan lil ‘alamin (a mercy to all creation). The objectives were: (1) to provide preachers with knowledge for professional preaching; (2) to introduce and deepen understanding of preaching strategies and designs; and (3) to counter radicalism and intolerance. The activity aimed to produce preachers capable of implementing acceptable preaching methods. The counseling had a positive and significant impact, evidenced by increased knowledge, behavioral changes, and strengthened community capacity. Overall, this community service activity through dialogue yielded broad and diverse impacts, benefiting both the community and the organizers.